Categorizing Susceptibility of Clinical Isolates of Candida auris to Amphotericin B, Caspofungin, and Fluconazole by Use of the CLSI M44-A2 Disk Diffusion Method - Nunnally, Natalie S. (J Clin Microbiol, 2021)
We evaluated the CLSI M44ed3E disk diffusion method compared with the CLSI M27ed4 broth microdilution method for caspofungin and fluconazole and the Etest method for amphotericin B to categorize susceptibility of 347 clinical isolates of Candida auris. Utilizing the zone diameter cutoffs established here, we observed overall categorical agreement between the two methods. For caspofungin, concordant results were observed for 98% of isolates, with <1% very major and 1% major errors. For fluconazole, concordant results were observed for 91% of isolates, with 1% very major and 8% major errors. For amphotericin B, concordant results were observed for 74% of isolates, with <1% very major errors and 25% major errors. The disk diffusion approach provides an accurate method for determining the susceptibility of C. auris for caspofungin and fluconazole and for identification of at least 75% of amphotericin B-susceptible isolates.